A fuzzy logic model to predict specific energy requirement for TBM performance prediction - Acaroglu, O.; Ozdemir, L.; Asbury, B. (Elsevier BV, 2008)
Prediction of tunnel boring machine performance is a critical key for successful tunnel excavations. Specific energy requirement of disc cutters, which is defined as the amount of energy required to excavate a unit volume of rock, is one of the important parameters used for performance prediction of these machines. Much research has been conducted to predict cutting parameters of disc cutters using analytical, empirical and numerical approaches. In recent years alternative methods, such as fuzzy logic, have been extensively used to deal with subjects having ambiguities and uncertainties. In this study, a model was established to predict specific energy requirement of constant cross-section disc cutters in the rock cutting process by using fuzzy logic method. This model is based on experience and the database which consists of linear cutting test results that were generated over for many years at the Earth Mechanics Institute of the Colorado School of Mines. The model predicts specific energy requirements of disc cutters using uniaxial compressive and tensile strength of rocks, disc diameter and tip width, penetration and spacing of cuts.